Ways of Perception. On Visual and Intercultural Perception/The Voice of the Visual. Visual Learning Strategies for Problem Analysis. Social Dialogue and Mediated Participation. - Plencovich, Maria Cristina (Journal of Agricultural Education & Extension, 2011)
The article reviews the books "Ways of Perception. On Visual and Intercultural Perception," by Hans Durrer and "The Voice of the Visual. Visual Learning Strategies for Problem Analysis. Social Dialogue and Mediated Participation," by Loes Witteveen.